Studying the Circulation of Etiological Agent of Lyme Borreliosis in Stavropol Region - T. N. Orlova; N. F. Vasilenko; E. N. Afanasiev; I. V. Chumakova; I. V. Sannikova; A. N. Kulichenko (Проблемы особо опасных инфекций, 2008)
Using polymerase chain reaction with reverse transcription (RT-PCR) rRNA tick-borne borreliosis (Lyme borreliosis) etiological agent was detected in suspensions of ticks Ixodes ricinus. Infection rate was 7.1 %. Morbidity increase and substantially high level of Lyme borreliosis seroprevalence in the population of this region (3.9 %) evidence that Borrelia circulate in the territory of Stavropol region and ticks I. ricinus are vectors and the reservoir of the disease in this area. Monitoring of ixodes ticks quantity and their examination for carriage of Lyme borreliosis etiological agent will give the opportunity to forecast the possibility of infectioning people, living in enzootic territory.